Here's how to treat childhood apraxia of speech - Fish, Margaret A., 1959-; Skinder-Meredith, Amy (San Diego, CA : Plural Publishing, Inc., 2023)
"Here's How to Treat Childhood Apraxia of Speech, Third Edition is the most comprehensive textbook available addressing assessment, diagnosis, and treatment of childhood apraxia of speech (CAS). This text is the definitive reference for students and professionals seeking current best practices in treating children with CAS"--
What is CAS and Characteristics of CAS? -- Assessment and Differential Diagnosis of CAS -- Fundamentals of Treatment for CAS -- Evidence-Informed Decision Making in Treatment of CAS -- Establishing Vowel Accuracy and Natural Prosody -- Facilitating Speech and Language in Minimally Verbal Children -- Addressing Early Literacy Concerns in Children with CAS -- Supporting the Needs of Older Children with Ongoing Communication Challenges -- Treating Children with Comorbid Disorders -- Considerations in Treatment of CAS Via Telepractice -- The Changing Needs of Children Over Time -- Developing Meaningful Goals and Collecting Data -- Partnering with Parents to Maximize Treatment Outcomes.
Includes bibliographical references and index.
Keywords: Apraxias -- therapy; Speech Disorders -- therapy; Speech Therapy -- methods; Child